O sujeito do discurso: uma leitura de gênero das diretrizes para a educação na Igreja Metodista - Dorneles, Simone Silva (2006)
The Subject of Discourse is a reading of gender of the discourse of education for citizenship which is present in the Guidelines for Education in the Methodist Church. These guidelines are found in the Plan for the Life and Mission of the Church, a document which was approved in 1982 at the XIII General Conference of the Methodist Church. The theoretical reference chosen for a possible reading of gender is work produced in the area of Feminist Liberation Theology. Discourse analysis is used as a qualitative methodological research approach in Social Sciences. In this study, the critical feminist hermeneutical proposal of Elizabeth Schüssler Fiorenza and the language studies of Eni Puccinelli Orlandi are used in order to deconstruct and give meaning to the educational discourse of the document in question. The text is organized into three chapters, based upon critical feminist hermeneutics: See, Name and Reconstruct. In the first chapter, See represents a visualization of the educational history of the Methodist Church; in the second chapter, Name implies the identification of the branches of discourse which characterize the document inspired by Liberation Theology and Brazilian pedagogical tradition; in the third chapter, Reconstruct means a rereading of the discourse of education for citizenship from the perspectives of Feminist Liberation Theology. A reading of gender of the Guidelines for Education is a suspect exercise in relation to the document s construction of discourse. This conjecture was transformed into a premise and thus oriented this study by asking the text about the subject that articulates this evangelical religious confession s discourse of education for citizenship.